2019
DOI: 10.1111/joim.12891
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Cortisol – predictors of treatment response to corticosteroids in community‐acquired pneumonia?

Abstract: Urwyler

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Corticosteroids may be a double-edged sword in the management of immunomodulation and inflammatory response. Its pharmacological mechanisms involve reducing inflammatory cytokines production, leukocyte infiltration and phagocytosis at the onset of inflammation (29,30). Besides, the corticosteroid can interfere with the interaction between proinflammatory factors (31,32).…”
Section: The Onset Time Of Crs and Administration Time Of Corticosteroids/ Tocilizumab Were Associated With Severity Of Crs And Cardiac Dmentioning
confidence: 99%
“…Corticosteroids may be a double-edged sword in the management of immunomodulation and inflammatory response. Its pharmacological mechanisms involve reducing inflammatory cytokines production, leukocyte infiltration and phagocytosis at the onset of inflammation (29,30). Besides, the corticosteroid can interfere with the interaction between proinflammatory factors (31,32).…”
Section: The Onset Time Of Crs and Administration Time Of Corticosteroids/ Tocilizumab Were Associated With Severity Of Crs And Cardiac Dmentioning
confidence: 99%
“…10,11 More information is necessary given that variation in the inflammatory pattern by different variables may impact prognosis and patient selection for future studies of biomarker-guided therapy, which may improve outcomes in patients with CAP. 12 Adequate classification is critical to the clinical applicability of personalized medicine in diagnostics and prognostics for CAP and sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore necessary to increase our knowledge of the host response and pattern of inflammatory marker response in CAP, but information about levels of some biomarkers by sociodemographic features in the host is scarce 10,11 . More information is necessary given that variation in the inflammatory pattern by different variables may impact prognosis and patient selection for future studies of biomarker‐guided therapy, which may improve outcomes in patients with CAP 12 . Adequate classification is critical to the clinical applicability of personalized medicine in diagnostics and prognostics for CAP and sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cortisol, as a marker of adrenal function, has demonstrated that it may help in prognosis prediction [99][100][101]. In addition, its measurement could identify the response of patients to steroids [102]. Meanwhile, high levels of the fibroblast growth factor 21 (FGF21) have recently been related to poor short-term prognosis in CAP patients from two randomised clinical trials [121].…”
Section: Othersmentioning
confidence: 99%